Kalibrasi Arah Kiblat Masjid Di Kecamatan Petir Dengan Metode Segitiga Siku-Siku Dari Bayangan Matahari - Ahdi, Hapizul; Faozi, Irfan; Alamsyah, Alamsyah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the accuracy of the qibla direction of mosques in the Petir subdistrict. From observations made using Google Earth, many mosques do not face the Kaaba. When investigating the mosques that were indicated to be misaligned, it was found that the mosque management boards had not yet made any efforts to remeasure the qibla direction. This serves as the basis for the researcher to investigate the accuracy of the qibla direction of mosques in Petir subdistrict. This study employs a field research method. Primary data sources include interviews with ten mosque management committee (DKM) chairpersons. Data collection techniques included observation, interviews, and direct measurement of the qibla direction of the mosques. For the accuracy test of the qibla direction, the researcher used the right-angle triangle method based on the shadow of the sun. After the data was obtained, it was analyzed using qualitative descriptive techniques. The results of the study revealed that out of the ten mosques studied, only one mosque used the rubu’ mujayyab method to determine the qibla direction, while the other nine used a compass. The accuracy of the qibla direction in mosques in Petir Subdistrict shows considerable variation; one mosque is categorized as accurate, eight mosques are less accurate, and one mosque is inaccurate. This deviation occurs because during the initial measurement for mosque construction, accurate data and methods were not used. Therefore, prayers performed in mosques with inaccurate qibla directions are invalid according to the opinion of Imam Shafi'i. For this reason, it is necessary to adjust the qibla direction in accordance with the calibration results.